A Way to Close the Loop: Physicochemical and Adsorbing Properties of Soybean Hulls Recovered After Soybean Peroxidase Extraction - Tummino, Maria Laura; Tolardo, Valentina; Malandrino, Mery; Sadraei, Razieh; Magnacca, Giuliana; Laurenti, Enzo (Frontiers in Chemistry, 2020)
Soybean hulls are one of the by-products of soybean crushing and find application mainly in the animal feed sector. Nevertheless, soybean hulls have been already exploited as source of peroxidase (soybean peroxidase, SBP), an enzyme adopted in a wide range of applications such as bioremediation and wastewater treatment, biocatalysis, diagnostic tests, therapeutics and biosensors. In this work, the soybean hulls after the SBP extraction, destined to become a putrescible waste, were recovered and employed as adsorbents for water remediation due to their cellulose-based composition. They were studied from a physicochemical point of view using different characterization techniques and applied for the adsorption of five inorganic ions (Fe(III), Al(III), Cr(III), Ni(II) and Mn(II)) in different aqueous matrixes. The behavior of the exhausted soybean hulls was compared to pristine hulls, demonstrating better performances as pollutant adsorbents despite significant changes in their features, especially in terms of surface morphology, charge and composition. Overall, this work evidences that these kinds of double-recovered scraps are an effective and sustainable alternative for metal contaminants removal from water.